Regional Passenger Rail Efficiency: Measurement and Explanation in the Case of France. (1st January 2023) - Desmaris, Christian; Monchambert, Guillaume
This paper investigates the productive efficiency of French regional rail operators. Benefiting from unique databases, we use a panel stochastic frontier model to measure and explain the productive efficiency. We consider the regional monopoly nature of these operators by introducing specific contract-related variables. Technical efficiency level ranges from 59 to 98 per cent, revealing a high degree of heterogeneity in productive performance between regional operators. Factors related to the societal environment, characteristics of the rail system and contractual design are significantly correlated with the technical efficiency. Policy implications of these results are substantial for both public authorities and rail operators.